2021
DOI: 10.1007/s00417-021-05339-1
|View full text |Cite
|
Sign up to set email alerts
|

18 F-FDG-PET/MRI in patients with Graves’ orbitopathy.

Abstract: Purpose Currently, therapeutic management of patients with Graves’ orbitopathy (GO) relies on clinical assessments and MRI. However, monitoring of inflammation remains difficult since external inflammatory signs do not necessarily represent the orbital disease activity. Therefore, we aimed to evaluate the diagnostic value of 18F-FDG-PET/MRI to assess the inflammation of GO patients. Methods Enrolled patients with new onset of GO underwent ophthalmological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Heterogeneity has not only been reported for clinical and radiological findings in EO, but also different imaging modalities including MRI and PET (alone or in combination with MRI or CT) have been used to study various morphological and functional parameters. In a recently published work, Weber et al reported PET-MRI to be suited for the assessment of EO inflammation and to be a good discriminator for severe vs. mild-to-moderate EO 25 . A variety of other parameters have been analyzed in EO in numerous other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity has not only been reported for clinical and radiological findings in EO, but also different imaging modalities including MRI and PET (alone or in combination with MRI or CT) have been used to study various morphological and functional parameters. In a recently published work, Weber et al reported PET-MRI to be suited for the assessment of EO inflammation and to be a good discriminator for severe vs. mild-to-moderate EO 25 . A variety of other parameters have been analyzed in EO in numerous other studies.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, while cost and patient accessibility pose current challenges ( 81 ), ongoing efforts to enhance SPECT’s availability, coupled with its evolving performance, underscore its potential in predicting responses to anti-inflammatory treatments in patients with TED. In comparison, research progress of PET is still restricted to disease diagnosis and monitoring, which might be mainly due to lack of sample size in PET examination ( 82 , 83 ). Nevertheless, recent research has revealed the potential of Zirconium-89-rituximab PET/CT as a predictive marker for rituximab treatment response in TED ( 84 , 85 ), which might provide insights for future research into further exploring the potency of PET in predicting anti-inflammatory treatment response.…”
Section: Imaging Biomarkersmentioning
confidence: 99%
“…PET/MRI is currently not recommended for clinical use but it can serve as an academic tool to explain the pathophysiology of GO. Technical progress towards shorter protocols and new tracers that are less sensitive to confounding might enable the diagnosis of GO in PET/ MRI in the future (36).…”
Section: Fdg-pet/mrimentioning
confidence: 99%